2008
DOI: 10.1103/physrevb.78.115322
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of bismuth telluride nanowires in the constant relaxation-time approximation

Abstract: Electronic structure of bismuth telluride nanowires with the growth directions [110] and [015] is studied in the framework of the anisotropic effective mass method using the parabolic band approximation. The components of the electron and hole effective mass tensors for six valleys are calculated for both growth directions. For a square nanowire, in the temperature range from 77 K to 500 K, the dependence of the Seebeck coefficient S, the thermal κ and electrical conductivity σ as well as the figure of meri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 40 publications
1
57
0
Order By: Relevance
“…Single-crystal studies have reported an even larger hole mobility (8 × 10 3 cm 2 V −1 s −1 ) in unfilled Rh 4 Sb 12 [23]. In contrast, the hole and electron mobility ratios in intrinsic Bi 2 Te 3 and Si, both known to show appreciable bipolar thermal diffusion, are one to two orders of magnitude less than the skutterudites [21,24,25]. Therefore, it is likely that a vast disparity in hole and electron mobility in completely intrinsic Rh 4 Sb 12 prohibits appreciable bipolar thermal diffusion as only one charge carrier (holes) likely dominates the electrical conductivity (Eq.…”
Section: Thermal Conductivitymentioning
confidence: 82%
“…Single-crystal studies have reported an even larger hole mobility (8 × 10 3 cm 2 V −1 s −1 ) in unfilled Rh 4 Sb 12 [23]. In contrast, the hole and electron mobility ratios in intrinsic Bi 2 Te 3 and Si, both known to show appreciable bipolar thermal diffusion, are one to two orders of magnitude less than the skutterudites [21,24,25]. Therefore, it is likely that a vast disparity in hole and electron mobility in completely intrinsic Rh 4 Sb 12 prohibits appreciable bipolar thermal diffusion as only one charge carrier (holes) likely dominates the electrical conductivity (Eq.…”
Section: Thermal Conductivitymentioning
confidence: 82%
“…In recent years, various methods have been applied to synthesize nanostructured thermoelectric materials, [3][4][5][6] and extensive experimental work has been performed with particular focus on their electronic and thermal properties. [7][8][9] However, the mechanical properties of such nanowires are not known in detail. The immense potential of Bi 2 Te 3 nanowires has called for research into their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effective mass approximation and the k.p theory were widely used for transport calculations. [7][8][9][10] These approaches become questionable for nanowires, at least if their diameter is just a few lattice constants. Atomistic methods, such as the tight-binding (TB) electronic structure approach or density functional theory calculations, should be used instead.…”
Section: Introductionmentioning
confidence: 99%